USE OF MALAY-ARABIC SCRIPTURES OF JAWI/PEGON IN NUMBER OF ANCIENT METAL CURRENCIES IN INDONESIA FROM PRE-INDEPENDENCE TO EARLY INDEPENDENCE - Agung Gumilar (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2021)
Currency since the early times has a significant historical value, it was representing the culture from different periods. The Jawi/Pegon script has in long term isues since the emergence of Islam to the Nusantara archipelago in 7th century CE. This script can be found in Indonesian old coins which dated from 13th Century CE until the early Indonesian Republic in the first half of 20th Century. Therefore, it is important to do a research for the existence of the Arab-Malay scipt through coins. Moreover, deeper research is needed to know its true role in history. It is very necessary to do because the Arab Jawi/Pegon script as a part of the Nusantara cultural heritage has been “forgotten” for so long time. In studying the Arab Jawi/Pegon script existence and its role in old Indonesian monetary system, the writer prefers using literature studies. It means that this article will focused on library research because the analysis is directed the books and writings related to the discussion.